Menyingkap Makna Objek Pendidikan dalam Istilah al-Ahl, al-‘Asyirah, dan al-Aqrab - Musaddad Harahap; Munzir Hitami; Abu Anwar (DAYAH: Journal of Islamic Education, 2022)
The problem in this study is the importance of understanding the nature of the object of education from the perspective of Islamic education. In general, the object of education is often understood as just a human who needs learning. But in Islamic education, the object of education is not just individual humans, but more than that. Humans as objects of education have very broad dimensions. Islamic education has indicated this in its main source, namely the Qur'an and the Sunnah of the Prophet Muhammad. To answer this research problem, the approach used is library research. The results of this study are the object of education in Islam refers to several words. First, the word ahl means family, wife, relatives, or people who live in the same place. the word ahl can also refer to various groups that are formed and formed in the reality of human life. Second, the word 'asyirah has varied meanings. The emphasis on the meaning of the most dominant is the family in a larger scope when compared to the family in terms of ahl. So that the term 'asyirah is not only limited to a relationship because of kinship, but also a relationship because of similarities both geographically or in terms of place of residence, ethnicity, tribe, or because of the intense interactive communication between existing community groups. Third, the term al-qurbu refers more to a family bound by brotherhood, perhaps the brotherhood is the result of a lineage or brotherhood which is only limited to common perception. Thus, in Islamic education, education does not only focus on how to teach humans as individuals, but humans in various communities also receive serious attention in order to realize the goals of Islamic education, namely the actualization of faith and piety to Allah SWT in human’s soul.